Pengembangan Media Pembelajaran Drill and Practice Pada Materi Algoritma Pemrograman Untuk Siswa Kelas X SMA Negeri 2 Pontianak - Adewyah; Dewi Sulistiyarini; Febrianto Sabirin, (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2024)
The Merdeka Curriculum brings significant changes to the approaches, strategies, methods, and models of learning. One of the most notable changes can be seen in the Informatics subject. The Algorithm and Programming material is part of the Informatics subject, emphasizing students' ability to develop an application. Unfortunately, SMA N 2 Pontianak faces limitations in computer availability, which hampers the learning process for the Algorithm and Programming material. Therefore, this research aims to develop a feasible learning media using the drill-and-practice approach to support learning activities for the Algorithm and Programming material at SMA N 2 Pontianak. Additionally, this study seeks to understand the responses from users after utilizing the developed learning media. The research method used is the Research and Development (R&D) method with the ADDIE approach. The instruments used include interview guidelines, questionnaires, and documents. The data analysis was conducted using descriptive qualitative and quantitative analysis. The results indicate that the drill-and-practice learning media for the Algorithm and Programming material is effective and appropriate for its intended purpose. Keywords: Development, Drill and Practice, Web, Programming Algorithms